Sovereignty regionalised : an analysis of sovereignty and regionalism in ASEAN - Ekeroth, Mette (2008)
The present dissertation provides a post-structuralist discourse analysis of academic and political texts on ASEAN and illustrates how regionalism is framed as the condition of sovereignty in Southeast Asia.